STRUCTUROGENETIC ANALYSIS IN KOROSTISHIV TYPE PORPHYROBLASTIC GRANITES OF UKRAINIAN SHIELD - PAVLOVA, O.; BUBNOVA, O.; FILIPOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Stages of structural transformation (structural evolution) of Korostishiv granites the Northwest part of the Ukrainian Shield have been established as a result of structural and microtectonic analysis. Genetic groups of structural elements (magmatic, metasomatic, deformative (tectonic)) have been allocated. The microstructure of some minerals is considered and their place in the rock formation history is determined.